Discussion of “Energy Dissipation and Turbulent Production in Weak Hydraulic Jumps” by E. Mignot and R. Cienfuegos - Romagnoli, Martín (2011)
The authors reported experimental results on the spatial evolution of turbulent kinetic energy and turbulence production in free weak hydraulic jumps. They performed turbulence measurements using two different 16 MHz SonTek/YSI microacoustic Doppler velocimeters (ADVs) on hydraulic jumps for inflow Froude numbers (F1) of 1.3, 1.9, and 2 [F1 ¼ U1=ðz1gÞ0:5, where U1 = inflow mean velocity; z1 = supercritical depth; and g = gravitational acceleration]. Herein the discussers aim to complement the authors’ analysis by using a new independent data set and by arguing both the bias on the estimated values of turbulent kinetic energy because of the effects of the ADV sampling strategy and the uncertainty on the experimental determination of the turbulence production term.